Tcl/Tk programming for the absolute beginner - Wall, Kurt (Thomson Course Technology, 2008)
A guide to Tcl/TK programming covers such topics as strings, working with lists, creating arrays, writing Tcl procedures, accessing files and directories, button widgets, and frames.